“Apelando para a justiça de Deus, na voz da História”: a fabricação de passados por padres em Sobral (1922 - 1991) - Rocha, Thiago Braga Teles da (2023)
Throughout its history, the city of Sobral was presented by different social actors as a model. This movement has a great relation with the historiographical narratives that were produced, especially, by clerics during the 20th century. In this work, we study texts written by Catholic priests responsible for fabricating pasts about the city of Sobral, through historiography and other genres, such as biographies, genealogies and memoirs, published between the years 1922 and 1991. Such texts are treated as references for contemporary historiography and for the public power and were fundamental for the construction of identities and for the ordering of time in Sobral. The social place, the practice and the writing of the works of five clerics (Fortunato Alves Linhares, Vicente Martins da Costa, dom José Tupinambá da Frota, João Mendes Lira and Francisco Sadoc de Araújo), divided into two generations, are analyzed, problematizing, from the respective historiographical operations, the definitions of archives, the constructions of concepts and the consolidation of historiographical narratives that provided the assembly of images about the city of Sobral that were appropriated, over time, by the public power, consolidating idealized visions of a model city, Catholic and white, which should have its model exported to other spatialities. In the first chapter, we study the protagonists of the writing of history in the city, trying to understand the social place of each one. In the following chapter, an analysis is carried out on the historiographical work done by the clerics, entering the practice and the writing of history. In the third chapter, the construction of associated self-images is analysed, which help to compose the concept of sobralidade, fundamental to politics in Sobral. Finally, in the fourth chapter, we reflect about the production of discourses in history, and the use of these by the public power, about the expeditions to verify the Theory of Relativity, in the year 1919.